Trilobatin, a Naturally Occurring Food Additive, Ameliorates Exhaustive Exercise-Induced Fatigue in Mice: Involvement of Nrf2/ARE/Ferroptosis Signaling Pathway - Xiao, Ran; Wei, Yu; Zhang, Yueping; Xu, Fan; Ma, Congjian; Gong, Qihai; Gao, Jianmei; Xu, Yingshu (Frontiers in Pharmacology, 2022)
Nrf2-mediatied oxidative stress is a promising target of exhaustive exercise-induced fatigue (EEIF). Trilobatin (TLB) is a naturally occurring food additive with anti-oxidant effect and Nrf2 activation potency. The present study was aimed to investigate the effect of TLB on EEIF and elucidate its underlying mechanism. Our results showed that TLB exerted potent anti-EEIF effect, as reflected by rope climbing test and exhaustive swimming test. Moreover, TLB also effectively reduced the levels of lactate, creatine kinase and blood urea nitrogen, and increased liver glycogen and skeletal muscle glycogen in mice after EEIF insult. Additionally, TLB also balanced the redox status as evidenced by decreasing the generation of reactive oxygen species and improving the antioxidant enzymes activities including superoxide dismutase, catalase, glutathion peroxidase, as well as the level of glutathione both in tissue of muscle and myocardium. Furthermore, TLB promoted nuclear factor erythroid 2-related factor 2 (Nrf2) from cytoplasm to nucleus, and up-regulated its downstream antioxidant response element (ARE) including quinone oxidoreductase-1 and heme oxygenase-1. Intriguingly, TLB also up-regulated the GPx4 protein expression and reduced iron overload in mice after EEIF insult. Encouragingly, the benefical effect of TLB on EEIF-induced oxidative stress and ferroptosis were substantially abolished in Nrf2-deficiency mice. In conclusion, our findings demonstrate, for the first time, that TLB alleviates EEIF-induced oxidative stress through mediating Nrf2/ARE/ferroptosis axis